2011
DOI: 10.4309/jgi.2011.26.9
|View full text |Cite
|
Sign up to set email alerts
|

Fantasy baseball: A new way to gamble or just another game?

Abstract: The controversy over whether fantasy sports should be considered a new form of gambling was investigated. The predominance rule was used to operationally define gambling. This rule states that an activity is gambling if outcomes are due more to chance than to skill. Individuals active in a fantasy baseball league (commonly referred to as "owners") and individuals who had never entered any type of fantasy league ("non-owners") participated. Perceptions of skill-to-chance ratios were assessed and a content analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Only one study focused on pool/fantasy league bettors (Weiss, Demski, & Backen, 2011). Participants (N = 56) were mostly men (98.2%), with a mean age of 32.5 years, and bet on baseball.…”
Section: Pool/fantasy League Bettorsmentioning
confidence: 99%
“…Only one study focused on pool/fantasy league bettors (Weiss, Demski, & Backen, 2011). Participants (N = 56) were mostly men (98.2%), with a mean age of 32.5 years, and bet on baseball.…”
Section: Pool/fantasy League Bettorsmentioning
confidence: 99%
“… Weiss et al (2011) found that, based on perceptions of 'skill-to-chance' ratios, fantasy sport should not be considered gambling.…”
Section: Thementioning
confidence: 99%
“…Since gambling is a complex phenomenon, "chance--skill" analytical distinction, first raised by Caillois 1 Although there is much debate on how to define, assess, and understand gambling (see also Reith 1999;Curtis and Wilson 2001;Weiss, Demski, and Backen 2011), for the purposes of this paper, the term gambling is confined to its conventional meaning. The definition adopted here is that of sociologist Edward Devereux (1968) who referred to gambling as an "activity in which the parties involved, who are known as bettors or players, voluntarily engage to make the transfer of money or something else of value among themselves contingent upon the outcome of some future and uncertain event" (p. 53).…”
Section: Marina D'agatimentioning
confidence: 99%